The Environmental Conditions Behind the Formation of Small (subLCL) Clouds. Issue 23 (29th November 2021) - Altaratz, Orit; Koren, Ilan; Agassi, Eyal; Hirsch, Eitan; Levi, Yoav; Stav, Nir
Abstract: SubLCL clouds are defined here as clouds that form below the estimated lifting condensation level (LCL), on days that are predicted to be cloud‐free. On more than 50% of those days we observed clouds. Measurements of thermodynamic and sky conditions are used here together with numerical simulations to study subLCL clouds' formation. It was previously demonstrated that humidified parcels in mid‐boundary layer (BL) are likely to be the driving mechanism. We found the height of the LCL above the BL top and the RH near the BL top to be good predictors of the appearance of these clouds. In addition, the average change in RH in the rising parcels that form them was found to have a specific constant value (4.4  + ‾  0.2[%] per 100 m of elevation). This value enables the prediction of subLCL clouds' formation on days that rising parcels can reach saturation while moving up in the BL. Plain Language Summary: The thermodynamic conditions in a specific time and location (like temperature and humidity) determine if clouds can form. Nevertheless, there are days when a simple examination of the thermodynamic conditions predicts a cloud‐free sky but clouds do form. In this study, we examine in detail those days. We use observational datasets of sky and thermodynamic conditions over the Eastern Mediterranean summer, together with numerical cloud simulations for examination of those special days, when we observe warm clouds formation. We study what are the thermodynamic conditions that support their formation. Key Points: SubLCL clouds can form on days that are predicted to be cloud free (days in which the LCL is located above the boundary layer (BL)) The height of the LCL above the BL top and the RH near the BL top are good predictors for subLCL clouds' formation The change in RH in rising parcels that form subLCL clouds is uniform; hence, it enables the prediction of their chance of formation